Low Rates of Return to Play and Reduced Levels of Performance in Athletes Participating in the National Football League Following Acute Achilles Tendon Ruptures: A Systematic Review - James J. Butler MB BCh BAO; Davis Hedbany BS; Luilly Vargas MD; Matthew T. Kingery MD; Charles Lin MD; Alan P. Samsonov BS; John G. Kennedy MD, MCh, MMSc, FFSEM, FRCS (Orth) (Foot & Ankle Orthopaedics)
Category: Sports; Other Introduction/Purpose: The purpose of this systematic review was to evaluate rates of return to play and levels of performance following acute Achilles tendon ruptures (AATR) in the National Football League (NFL). Additionally, we sought to determine the prevalence rates of AATR and identify any risk factors for the development of AATR. Methods: During November 2023, the PubMed, Embase and Cochrane library databases were systematically reviewed to identify clinical studies examining outcomes following treatment of acute Achilles tendon ruptures (AATR) in the NFL. Twelve studies were included. Results: In total, 676 players (698 Achilles) sustained an AATR in the NFL. The playing positions that sustained the highest rates of AATRs was linebackers (19.0%), wide receivers (11.9%) and running backs (9.0%). 139 AATRs (50.4%) occurred in the preseason, 135 AATRs (48.9%) occurred during the regular season and 2 AATRs (0.7%) occurred during a post-season game. Playing surface was not associated with an increased risk of AATR. The return to play rate was 66.2% at a weighted mean time of 10.9±1.3 months. The mean number of games played per season following AATR was 12.9 games and the weighted mean career length following AATR was 2.2 ± 0.8 seasons. Overall, player performance deteriorated significantly following AATR, as demonstrated by lower power rankings and position specific metrics. Conclusion: This systematic review found was that the proportion of athletes participating in the NFL who returned to play following AATR was 66.2%. Both the mean number of games played per season and the mean number of seasons played decreased significantly following AATR. Overall, player performance deteriorated following AATR, regardless of player position. This study reinforces the potentially devastating sequelae following AATR in the elite athletic population.